MENINGKATKAN NILAI EKONOMI DENGAN PEMANFAATAN LIMBAH KOTORAN KAMBING SEBAGAI TAMBAHAN PUPUK ORGANIK - Mochammad Heru Widodo; Machrus Ali (Yayasan Education and Social Center, 2023)
Sebani Village, Sumobito District, Jombang Regency is a village where the majority of the population relies on the economy from the agricultural sector. However, in the implementation of agriculture, this village has not maximally utilized natural products, in this case goat manure, as a basic ingredient for organic fertilizer which is used in its own farming or traded. So that this community service report aims that the people of Sebani Village can make compost made from goat manure to improve agriculture and the community's economy. The community service method is carried out in three stages; preparation stage, socialization and application stage, as well as the final stage. The preparatory stage is carried out by making composting modules. The socialization stage was carried out in community meetings and special socialization, as well as training in making compost from fermentation using EM4 and additional rice bran in goat manure. The final stage consists of preparing the final report. The expected result is that the people of Sebani Village are able to make solid compost made from goat manure which can be used in agriculture, as well as commercialized so that it can improve the community's economy